Music as Labour Inequalities and Activism in the Past and Present - Abfalter, Dagmar; Reitsamer, Rosa (Routledge Research in the Creative and Cultural Industries, 2022)
This book brings together research at the intersection of music, cultural industries, management, antiracist politics and gender studies to analyse music as labour, in particular highlighting social inequalities and activism. Providing insights into labour processes and practices, the authors investigate the changing role of manifold actors, institutions and technologies and the corresponding shifts in the valuation and evaluation of music achievements that have shaped the relationship between music, labour, the economy and politics. With research into a variety of geographic regions, chapters shed light on the various ways by which musicians' work is performed, constructed and managed at different times and show that musicians' working practices have been marked by precarity, insecurity and short-term contracts long before capitalism invited everybody to 'be creative'. In doing so, they specifically examine the dynamics in music professions and educational institutions, as well as gatekeepers and mechanisms of inclusion and exclusion. With a specific emphasis on inequalities in the music industries, this book will be essential reading for scholars seeking to understand the collective actions and initiatives that foster participation, inclusion, diversity and fair pay amongst musicians and other workers.